NFIA differentially controls adipogenic and myogenic gene program through distinct pathways to ensure brown and beige adipocyte differentiation - Hiraike, Yuta (PLoS Genet, 2020)
The transcription factor nuclear factor I-A (NFIA) is a regulator of brown adipocyte differentiation. Here we show that the C-terminal 17 amino acid residues of NFIA (which we call pro#3 domain) are required for the transcriptional activity of NFIA. Full-length NFIA—but not deletion mutant lacking pro#3 domain—rescued impaired expression of PPARγ, the master transcriptional regulator of adipogenesis and impaired adipocyte differentiation in NFIA-knockout cells. Mechanistically, the ability of NFIA to penetrate chromatin and bind to the crucial Pparg enhancer is mediated through pro#3 domain. However, the deletion mutant still binds to Myod1 enhancer to repress expression of MyoD, the master transcriptional regulator of myogenesis as well as proximally transcribed non-coding RNA called (DRR)eRNA, via competition with KLF5 in terms of enhancer binding, leading to suppression of myogenic gene program. Therefore, the negative effect of NFIA on the myogenic gene program is, at least partly, independent of the positive effect on PPARγ expression and its downstream adipogenic gene program. These results uncover multiple ways of action of NFIA to ensure optimal regulation of brown and beige adipocyte differentiation.